Optimisation of Production Under Uncertainty The State-Contingent Approach - Rasmussen, Svend (SpringerBriefs in Economics, 2011)
The book provides a short review of the classical approach to planning and decision making under uncertainty. It further explains the concept of state-contingent goods, and it extends earlier work on the state-contingent approach to describing production under uncertainty to the problems involved in optimising production under uncertainty.